A comprehensive review on polymer single crystals—From fundamental concepts to applications. (June 2018) - Agbolaghi, Samira; Abbaspoor, Saleheh; Abbasi, Farhang
Abstract: Polymer single crystals and correlated crystalline structures are reviewed by emphasizing the last 10–20 years of research on fundamental concepts, single crystal engineering, and applications. The review commences with basic work comprising morphologies, theories, and especial single crystals, subsequently passes to star block, brush-covered, well-oriented, patterned, epitaxial, non-flat and degradable single crystals, and eventually reviews single crystals and nano-particles/structures including magnetically recyclable catalyst supports, nano-hybrid shish-kebabs to mimic the natural bone nanostructures, and nano/micromotors. Other applications are also presented and discussed in detail, including exploiting conductive single crystals of poly(3-hexylthiophene-2, 5-diyl) and poly(3, 4-ethylenedioxythiophene) in field-effect transistors, nanowires and microwires, as well as fostering amino-functionalized lamellar poly(L-lactide) single crystals as a delivery system for human papillomaviruses-associated tumors.